ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI PROVINSI ACEH - Julia Saputri; Ichsan Ichsan (LPPM UNIMAL, 2022)
This study examined the effect of GDRP, government spending, and population on local revenue (PAD) in Aceh Province. This study used secondary data using 2015-2019 accessed on www.bps.go.id. The data analysis method used was panel data regression analysis using Eviews 9. The results of this study indicate that GDRP and government expenditures have no significant effect on PAD in Aceh Province. Meanwhile, the population had a positive and significant effect on PAD in Aceh Province. Simultaneously, GDRP, government spending, and the population had a positive and significant effect on PAD in Aceh Province. This study suggests district/city governments pay more attention to local tax revenues and regional levies that are required for the community to increase district/city local revenue (PAD) in Aceh Province.